1996
DOI: 10.1021/jp953256d
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of the Nonframework Cation Location and Distribution in Microporous Titanosilicate ETS-10

Abstract: The nonframework cation sites for K-ETS-10 and Na-ETS-10 have been modeled using molecular simulation techniques. This work combines a Monte Carlo packing procedure with lattice energy calculations, to simulate the charge-balancing cation sites in a titanosilicate, starting from only the framework structural data. One hundred trial packing arrangements for each cation type were randomly generated with the Monte Carlo procedure, and the lattice energy for each of these structures was calculated, considering ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 11 publications
4
34
1
Order By: Relevance
“…In a recent grand canonical Monte Carlo (GCMC) study of methane adsorption in Na-ETS-10 and Na-ETS-4 materials by Pillai et al, 38 the cation distribution and mobility in these materials was analyzed at methane pressures between 0 and 100000 kPa. In the case of Na-ETS-10 and in the absence of methane, the simulations by Pillai et al 38 confirmed the presence of extra-framework cations at the same sites identified in Grillo and Carraza's work, 36 e.g. I -IV.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…In a recent grand canonical Monte Carlo (GCMC) study of methane adsorption in Na-ETS-10 and Na-ETS-4 materials by Pillai et al, 38 the cation distribution and mobility in these materials was analyzed at methane pressures between 0 and 100000 kPa. In the case of Na-ETS-10 and in the absence of methane, the simulations by Pillai et al 38 confirmed the presence of extra-framework cations at the same sites identified in Grillo and Carraza's work, 36 e.g. I -IV.…”
Section: Methodssupporting
confidence: 56%
“…The terminating H atoms were placed at the same bond angles and dihedral angles as the corresponding Si or Ti atoms in the extended crystal structure, and at a bond distance of 0.96 Å, which is a typical value for this type of materials. 35 The initial positions of the cations (i.e., prior to the optimization procedure) employed to neutralize the system were taken from Grillo and Carraza, 36 who used molecular simulation to analyze cation locations in ETS-10 and obtained good agreement with experimental data of Wang and Jacobson. 37 These authors identified four different positions where cations are located (cf.…”
Section: Methodsmentioning
confidence: 99%
“…9, 43, 44 The starting geometry of the cluster corresponded to the coordinates reported by Anderson et al 2. Na + counterions were initially placed according to Grillo’s results 45. Hydrogen atoms were used to saturate the dangling SiO bonds at the periphery of the cluster and were kept fixed to orient it in the direction of the next Si site.…”
Section: Methodsmentioning
confidence: 99%
“…The cations are found distributed along the pore wall adjacent to the titania chains to compensate the anionic framework. 22,23 This unique structure is expected to result in different, and perhaps enhanced, ion transport compared to zeolites.…”
Section: Introductionmentioning
confidence: 99%